c.1 - Bhatt, V. V. (Bombay, 1963)
As Rostow has rightly emphasized, the most important pre-condition for sustained economic development is political, that is, the establishment of an effective modern government, sympathetic to the process of economic development. In all the countries, which completed their process of "take-off into self-sustained growth ", to use Rostow's eloquent phrase, before the First World War, this basic condition was satisfied. Further, at least during the initial stages of economic development, the State played a very vital role in all these countries. Of course, the magnitude of State action varied with the type of the historical environment of the different countries; the importance of the role of the State seems to have been an increasing function of the degree of relative economic backwardness of a country and the magnitude of the effort necessary for it to catch up with the other advanced countries.
Keywords: Economics